2022
DOI: 10.1021/acs.jafc.1c05121
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Tetracyclines by Fungi: Challenges and Future Research Perspectives

Abstract: Tetracycline antibiotics are used worldwide in human and veterinary medicine. On the basis of low metabolization and through organic fertilizers, tetracyclines enter the environment in a biologically active form. This can have toxic effects on microbial communities and promote the selection of resistant strains. The use of fungi could be a promising approach to deactivate tetracyclines by degradation or derivatization as a result of their particular enzyme endowment. Here, we highlight the current analytical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(64 reference statements)
0
4
0
1
Order By: Relevance
“…Crude lignin peroxidase ( Wen et al, 2009 ) or crude manganese peroxidase ( Wen et al, 2010 ) produced by Phanerochaete chrysosporium were also both used to degrade tetracycline and oxytetracycline in vitro and the degradation rates were up to 95% in 5 min. In more research investigations, the application of fungal cultures or their purified enzymes led to a reduction in tetracycline concentrations and mass spectrometry (MS) analyses indicated that the resultant transformation products primarily consisted of lower molecular weight metabolites ( Delius et al, 2022 ). Several studies have documented the biotransformation and inactivation of tetracyclines via pure bacterial isolates.…”
Section: Antibacterial Compoundsmentioning
confidence: 99%
“…Crude lignin peroxidase ( Wen et al, 2009 ) or crude manganese peroxidase ( Wen et al, 2010 ) produced by Phanerochaete chrysosporium were also both used to degrade tetracycline and oxytetracycline in vitro and the degradation rates were up to 95% in 5 min. In more research investigations, the application of fungal cultures or their purified enzymes led to a reduction in tetracycline concentrations and mass spectrometry (MS) analyses indicated that the resultant transformation products primarily consisted of lower molecular weight metabolites ( Delius et al, 2022 ). Several studies have documented the biotransformation and inactivation of tetracyclines via pure bacterial isolates.…”
Section: Antibacterial Compoundsmentioning
confidence: 99%
“…Over the past few decades, the overuse of antibiotics in the poultry farming industry to ensure high yields has aroused increasing public concern about the quality and safety of animal-derived foodstuffs such as milk. Thereinto, tetracycline antibiotics (TCs) are a class of tetraphenyl skeleton-based small molecular compounds that are recognized as one of the most low-cost and prominent broad-spectrum antibacterial activity, enabling them to be the most popular antibiotics against bacterial infections resulting from both Gram-positive and Gram-negative bacteria. Nevertheless, the excessive use of TCs unavoidably poses a residual risk in animal-derived foodstuffs such as milk, resulting in food safety issues. Long-term exposure to TCA residues has been reported to cause a range of health problems such as gastrointestinal disorders, nephrotoxicity, allergies, and central nervous system disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that terpenoids in plants have various functions, such as defense, disease resistance, allelopathy, and insect induction [18][19][20][21][22]. Research has also been conducted on terpenoid compounds in fungi [23][24][25][26][27], such as tetracyclines and pleuromutilin (Drosophilin B) [28,29]. In addition, terpenoids have important medicinal functions [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%